1998
DOI: 10.1016/s0924-9338(98)80141-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in schizophrenia: Long-term follow-up in 362 chronic Spanish schizophrenic outpatients undergoing risperidone maintenance treatment

Abstract: Our aim was to determine the effect of risperidone monotherapy treatment on disability and on the quality of life of 318 schizophrenic outpatients who had been previously treated with other neuroleptics. Patients were assessed at baseline 2, 4 and 8 months using the BPRS, CGI, WHO/DDS and SF-36. BPRS scores showed a significant decrease at month 2, both in the total score and in each of the three clusters, negative, positive and depression/anxiety. WHO/DDS scores significantly decreased both in the overall sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 13 publications
1
13
1
1
Order By: Relevance
“…Recent findings also substantiate the general notion that novel antipsychotic medications are uniformly better tolerated as indicated by the measures of self-rated quality of life [5,[23][24][25][26]. If these pharmacological properties are shown to be significant, the therapeutic implications could be far reaching in terms of improved compliance, relapse prevention, effective rehabilitation and enhanced quality of life [13,16,19,25,27]. There has been a growing need, however, not only to establish the therapeutic superiority of more recently developed medications over the conventional antipsychotic drugs, but also to explore the differential effectiveness of various individual compounds and their influence on the patients' subjective well-being [26,[28][29][30].…”
Section: Introductionsupporting
confidence: 57%
“…Recent findings also substantiate the general notion that novel antipsychotic medications are uniformly better tolerated as indicated by the measures of self-rated quality of life [5,[23][24][25][26]. If these pharmacological properties are shown to be significant, the therapeutic implications could be far reaching in terms of improved compliance, relapse prevention, effective rehabilitation and enhanced quality of life [13,16,19,25,27]. There has been a growing need, however, not only to establish the therapeutic superiority of more recently developed medications over the conventional antipsychotic drugs, but also to explore the differential effectiveness of various individual compounds and their influence on the patients' subjective well-being [26,[28][29][30].…”
Section: Introductionsupporting
confidence: 57%
“…The sample mean is 27.91, compared to 50.0 for the general U.S. population and 76.7 for the general population of Oaxaca and Sonora in Mexico. It is also lower than the 29.21 reported by Bobes and colleagues (2001) for 36 clients with OCD in Spain, below the mean reported for a sample of 362 Spanish outpatients with chronic schizophrenia (Bobes et al, 1998), and below the mean for 60 U.S. persons with OCD reported by Koran and colleagues (1996). This suggests that OCD has had a major negative impact on the lives of the six persons in the current sample.…”
Section: Discussioncontrasting
confidence: 54%
“…Linear, quadratic and higher order time trends were tested by including the time trend components time, time 2 , time 3 …”
Section: The Analysis Of Time Trendsmentioning
confidence: 99%
“…Therefore, the newer antipsychotic drugs are usually called 'atypical' while the older ones are called 'conventional'. Nevertheless, while some studies have found that atypical antipsychotic drugs had a more positive effect than conventional antipsychotic medications on the subjective quality of life of patients with schizophrenia [3], a similar number have failed to replicate these results [4][5][6][7][8]. Some authors suspected that the patients' subjective experience of antipsychotic treatment depends not only on the objective drug effects but also on other factors such as insight into the nature of the illness and the necessity of continuous medical treatment [9,10].…”
Section: Introductionmentioning
confidence: 99%